Methylprednisolone effects on serum biochemical factors (CRP, PCT, IL-6, TNF-a) in viral pneumonia - Zeng Hongping; Zhu Qi; Bai Shaoyu; Liu Jie; Ren Dengjie; Chen Xin (Journal of Medical Biochemistry, 2025)
Background: This study was performed to demonstrate the effects of methylprednisolone (MPS) and azithromycin treatment on serum biochemical factors and their impact on Serum Biochemical Factors (CRP, PCT, IL-6, TNF-a) prognosis in patients with viral pneumonia (VP). Methods: This was a non-randomised clinical trial study on 120 patients with VP admitted to our hospital who had received different doses of methylprednisolone for viral pneumonia. Subjects were collected in four groups of Controls (Ctrl), low-dose (40 mg MPS, L-MPS), medium-dose (80 mg MPS, M-MPS), and high-dose (120 mg MPS, H-MPS) groups. The therapeutic efficacy of each group was evaluated. C-reactive protein (CRP), procalcitonin (PCT), and interleukin-6 (IL-6) were detected. Pulmonary function parameters were assessed using a pulmonary function testing device. Adverse reactions (ARs) such as fever, nausea, vomiting, and gastrointestinal bleeding post-treatment were recorded. Results: The total effective rate (TER) post-treatment in the Ctrl group was 60.00%, which was inferior to that in the L-MPS group (76.67%), M-MPS group (90.00%), and H-MPS group (93.33%) (P<0.05). Disappearance time of CRP, PCT, IL-6, TNF-a, fever, cough, and X-ray infiltrates was reduced in L-MPS, M-MPS, and H-MPS groups relative to the Ctrl group (P<0.05), while FVC, MMEF, and PEF were increased (P<0.05). Disappearance time of CRP, PCT, IL-6, TNF-a, fever, cough, and X-ray infiltrates in M-MPS and H-MPS groups was inferior to that in the L-MPS group (P<0.05), while FVC, MMEF, and PEF were higher (P<0.05). Conclusions: Medium-dose (80 mg) MPS combined with azithromycin greatly reduces inflammatory cytokine levels, shortens the time to clinical symptom relief, and improves lung function and respiratory capacity, demonstrating significant efficacy in treating VP.